(untitled) (Journal of Fatima Jinnah Medical University, 2020)
Background: Around the globe esophagus carcinoma is the 8th most common cancer with the incidence of 456,000 cases yearly & it is the 6th cause of mortality due to cancer. It is the 7th most common malignancy in men and 6th most common malignancy in females of Karachi. Chemoradiation therapy followed by surgery is the standard strategy for the treatment of locally advanced esophageal cancer. However, optimization of radiation dose, technique, chemotherapy, and patient selection is necessary to maximize its benefits. The objective of this study is to investigate the pattern of clinical response after concurrent chemoradiotherapy in patients with esophagus carcinoma. Patients and methods: It was a longitudinal study conducted at the Department of Oncology of Jinnah Postgraduate Medical College from May 2017 to July 2018. The patients of age 19-70 years of either gender with histological proven esophagus carcinoma of stage IA-IIIB1 were included in the study. Patients with metastasis disease were excluded from the study. Every patient underwent full disease staging at baseline that included PET-computed tomographic (CT) scans, endoscopic ultrasonography, blood tests, and endoscopic biopsies. The cross trial2 was inducted in patients with lower and middle esophagus in which concurrent chemoradiotherapy was performed with radiations in which carboplatin and paclitaxel was given weekly. For the upper esophagus the RTOG 85-01 trial3 was inducted, in which concurrent chemoradiotherapy with cisplatin at day 1 and 5FU was administered on day 1 to 5. After 6 weeks at the end of chemoradiation, the clinical response was assessed on CT scan. The absence of visible tumor on CT scan and dysphagia was labelled as clinical complete response, a reduction of more than 30% of the tumor length on CT scan was labelled as partial response and appearance of new tumors or 30% increase in size of existence lesion was labelled as progression of disease and non-response, while patients with no change in index lesion was labelled as stable disease. Statistical analysis was performed using SPSS version 23. Results: Total of 70 patients were included in the study. The median age of the patients was 43.32±14.24 years. The partial clinical response was achieved in majority of the patients after concurrent chemoradiation therapy (CCRT) (55.7%). However, 14 patients achieved complete response, 10 patients showed stable disease, 6 patients expired and only one patient showed disease progression with metastases. Conclusion: The results showed that the achievement of complete clinical response was comparatively low after CCRT than partial response.